The Relationship Between Vocational Self-Concept Crystallization, Ego-Identity Status, and Occupational Indecision, as Mediated by Rational or Experiential Processing - Landine, Jeffrey R. (Canadian Journal of Counselling and Psychotherapy, 2016)
The cognitive information processing model provides a useful way of looking at career decision-making but lacks a body of empirical evidence to support the specific processes that make possible the effective use of information about self and the world of work. The research described here sought to identify the role of an experiential or rational thinking style in moderating the development of vocational self-concepts and a vocational identity. As suggested by the literature, crystallized vocational self-concepts and identity achievement were positively correlated with decreased career indecision. A significant positive correlation was found for both rational and experiential thinking and vocational self-concept crystallization. Moderate but significant negative correlations were found for rational and experiential thinking and career indecision. The results suggest that both thinking styles have an impact on the development of vocational self-concepts and vocational identity and that they have a mediating effect on the relationship between vocational self-concept development and career indecision.